PERAN ELITE POLITIK LOKAL DALAM UPAYA MENDUKUNG PEMEKARAN KABUPATEN PANTAR PROVINSI NTT - Welhelmina Selfina Beli (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
To establish New Autonomous Region, the roles of local political elites are very strong so that expansion policy can be realized. If we look at the dynamics of regional expansion in Indonesia, it has a noble motivation for the welfare of society, but the fact shows that the expansions were only used as the interests of the elites who were thirst for power. Their losses in local elections were used as the weapon to get new positions by struggling for expansion, or also used the issue of expansion as their commodity in regional election and legislative election campaigns. The method used in this study was more qualitative decriptive. The aim of this research was to map the local political elites and to analyze the roles of the local political elites in an effort to support the expansion of Pantar regency East Nusa Tenggara. Analysis conducted relying on primary data obtained through secondary document review and in-depth interview with competent sources. Keywords: Decentralization, Roles of Local Political Elites, Regional Expansion